Una mirada desde «la otra orilla»: explorando la influencia del Feminismo en la reforma del Estado a partir de los casos de España, Chile y Perú - Bensa Morales, Jessica Violeta (2018)
Even though studies on state feminism have focused on its effects on the feminist movement, or in the progress of the gender agenda, its opposite relation has remained less explored: how does feminism influences the state? In this article I analyze the Spaniard, Chilean and Peruvian cases from the late 1970s to the present in order to look over the relationships between state feminism and the state´s reform. I propose that these influences can be traced in at least three aspects: the reform of the welfare models, the introduction of new concepts and management tools, questioning the-so-called neutrality of New Public Management and the way in which transnational or global feminism policies are translated or indigenized in different state contexts.